2022
DOI: 10.1111/jocn.16522
|View full text |Cite
|
Sign up to set email alerts
|

How registered nurses are measuring respiratory rates in adult acute care health settings: An integrative review

Abstract: Aims and objectives This integrative review aimed to draw conclusions from evidence on how registered nurses are measuring respiratory rates for acute care patients. Background Despite the growing research supporting respiratory rate as an early indicator for clinical deterioration, respiratory rate has consistently been the least frequently measured and accurately documented vital sign. Design An integrative review. Methods A systematic literature search was conducted in June 2022 in four databases: CINAHL, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The rate of omission of respiratory rate from vital sign documentation ranges from 0.8%–81.5% (Kallioinen et al., 2021) and a number of studies in a 2019 systematic review on RRS and deteriorating patients report infrequent documentation of respiratory rate (Difonzo, 2019). A 2022 integrative review on nurses' measurement of respiratory rate highlighted issues that included high levels of bias, estimation and incorrect techniques; lack of knowledge and undervaluing the clinical significance of respiratory rate; and a tendency to substitute oxygen saturation for respiratory rate measurement (Palmer et al., 2023). Our findings suggest nurses have are not embedding respiratory rate documentation in practice with sufficient frequency, given that this finding was evident across all adult‐based settings and prior to all adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of omission of respiratory rate from vital sign documentation ranges from 0.8%–81.5% (Kallioinen et al., 2021) and a number of studies in a 2019 systematic review on RRS and deteriorating patients report infrequent documentation of respiratory rate (Difonzo, 2019). A 2022 integrative review on nurses' measurement of respiratory rate highlighted issues that included high levels of bias, estimation and incorrect techniques; lack of knowledge and undervaluing the clinical significance of respiratory rate; and a tendency to substitute oxygen saturation for respiratory rate measurement (Palmer et al., 2023). Our findings suggest nurses have are not embedding respiratory rate documentation in practice with sufficient frequency, given that this finding was evident across all adult‐based settings and prior to all adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory rate has been shown to be an early indicator of clinical deterioration, and derangements in this vital sign appears to be particularly important in the early detection and timely diagnosis of new ECOPDs (Yañez et al, 2012;Borel et al, 2015). In real-world frontline clinical practice, however, respiratory rate has been shown to be nearly universally under-measured and/or sub-optimally measured given that busy healthcare workers must balance their very limited time on a variety of critical patient-related tasks for a large number of patients (Flenady et al, 2017;Palmer et al, 2023). A study which investigated vital sign monitoring practices in 441 patient interactions across two inpatient wards, notably one of which was a respiratory ward, demonstrated that while oxygen saturation and body temperature were taken 95% and 87% of the time, respectively, across the 229 instances where vital signs were performed, respiratory rate was only measured 22% of the time (Cardona-Morrell et al, 2016).…”
Section: Respiratory Rate: Percent Of Useable Data and Correlationsmentioning
confidence: 99%
“…Another shortcoming of manual intermittent vital signs measurement by ward staff is the inaccuracy of respiratory rate measurement, one of the vital signs that is associated most with clinical deterioration [ 37 ]. This vital sign is often guessed or repeated from previous recordings [ 38 , 39 ].…”
Section: Initiatives To Detect and Prevent Death From Perioperative D...mentioning
confidence: 99%